Analysis of Energy Absorption of Soft Body Armor with Experimental Method and Finite Element Method Using STF (Shear Thickening Fluid) Composite Material - Agus Dwi Putra; Dewi Izzatus Tsamroh; Bella Cornelia Tjiptady (Universitas Merdeka Malang, 2023)
Body armor is personal protective equipment or shield clothing for soldiers that has existed since Roman times until now. The function of body armor is to protect the body from attacks by foreign objects by absorbing energy. Body armor must have ballistic resistance and stabbing resistance, however, body armor that is often found usually has a high anti-ballistic level but is low in receiving stabbing attacks. STF (Shear Thickening Fluid) is a composite material which is unique in that the viscosity level can change in a way that causes the liquid dispersion to become solid and allows for increased stabbing resistance. This research began by making Kevlar samples which were then mixed with STF and then subjected to tensile testing to obtain material properties that were useful for simulating with FEM. The simulation is intended to analyze the rate of energy absorption that occurs in the sample. The results show that the kinetic energy absorption rate of the bullet is absorbed at a viscosity of 87%. The small energy that occurs is also absorbed in the form of frictional resistance with a value of 11.9%. The identified comparison results show that in cases 1-3 the percentage of viscosity is high so it is viscous, whereas in case 4 the direct reflection of the viscosity is low so it is close to liquid.